Understanding Among Societal Groups as a Prerequisite for Constructive Conflict Handling in Sustainable Land Use Change - Judith-Maria Maruschke; Daniel Schiller (Sustainable Development, 2025)
Understanding the other's point of view is key to expanding sustainable agriculture beyond its current niche status in the context of climate change mitigation. This paper aims to identify societal groups based on their understanding of the agriculturally shaped environment and investigates associations between sociodemographic characteristics and understanding among these groups. The empirical data stem from a large-scale population survey in Western Pomerania, Germany, a prime example of a region with manifold land use conflicts. Cluster and regression analyses were applied. Three understanding profiles are identified: alienated from the agriculturally shaped environment, knowledge about sustainable land use, and conventional agriculture. Significant associations between sociodemographic characteristics and understanding profiles exist and are discussed, as well as the transformational potential between the understanding profiles. In conclusion, understanding profiles can serve as a basis for creating appropriate actions to overcome barriers to sustainable development and enable the transformative potential at the societal level.
Keywords: 330; cluster analysis/K-Means; environmental understanding; land use conflicts; multinomial logistic regression; SDG indicator; sustainable development; understanding profiles